Microstructures and Hardness of TIG Welded Experimental 57Fe15Cr25Ni Steel - Parikin, Parikin; Dani, Mohammad; Rivai, Abu Khalid; Ismoyo, Agus Hadi; Iskandar, Riza; Dimyati, Arbi (UI Scholars Hub, 2018)
The microstructures and hardness of tungsten inert gas (TIG) welded experimental 57Fe15Cr25Ni steel were investigated through optical–scanning electron microscopy analyses and with a hardness tester, respectively. The welding process restructured the constituent atoms into regular and irregular crystal lattices. Rapid cooling of the weld metal allowed the formation of a dendritic (columnar) structure, with porous grains. By contrast, slow cooling influenced HAZ and led to the formation of grain structures. The crystal lattice became more organized and larger than other zones. Meanwhile, the base metal formed circular nets that covered large area inside thick and thin grain boundaries. The diffraction patterns revealed texturing in the weld metal. The crystallite orientation changed from (111) to (200) and (220) planes. The weld metal profile broadened (amorphous) and had full width at half maximum (fwhm) value larger than those in HAZ and the base metal. The weld metal possessed hardness of 121 HV, which is slightly lower than the hardness of the base metal (130 HV). HAZ exhibited the highest hardness value (152 HV). Hardening was influenced by carbon and outer oxygen migration to the grain boundaries, which formed colonies, i.e., chromium carbide, aluminum carbide, aluminum oxide, silicone oxide, and silicon carbide (precipitation hardening). Welding (heat) may change the microstructure and hardness of HAZ and the weld metal region, which would be brittle and very critical in responding to applied loads.